2019
DOI: 10.1093/femsec/fiz183
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of carotenogenic microalgae in the White Sea polar region

Abstract: Carotenogenic microalgae are unicellular photosynthetic organisms with the ability to accumulate carotenoids. Carotenoid accumulation is a protective reaction against environmental stress factors, such as bright light, extreme temperatures, etc. It makes the survival of these microorganisms under harsh environmental conditions possible. The diversity of carotenogenic microalgae has been described in detail for Central Europe and North America, as well as for tropical and subtropical latitudes with relatively f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…With optimal elevation higher than 2,500, species include Planophila laetevirens (previously detected in various locations in the Alps as well as high latitudes; Schmidt and Darcy, 2015 ), Bracteococcus ruber (recently detected in alpine mountains in New Zealand; Novis and Visnovsky, 2012 ) and Spongiochloris spongiosa . Taxa known to accumulate high levels of carotenoids, such as Chromochloris zofingiensis ( Ye and Huang, 2020 ), Sanguina ( Procházková et al, 2019 ), or Bracteacoccus ( Chekanov et al, 2020 ) species were also found at high altitudes. Interestingly, in one occurrence at ∼3,000 m, Bracteacoccus aerius was detected.…”
Section: Discussionmentioning
confidence: 99%
“…With optimal elevation higher than 2,500, species include Planophila laetevirens (previously detected in various locations in the Alps as well as high latitudes; Schmidt and Darcy, 2015 ), Bracteococcus ruber (recently detected in alpine mountains in New Zealand; Novis and Visnovsky, 2012 ) and Spongiochloris spongiosa . Taxa known to accumulate high levels of carotenoids, such as Chromochloris zofingiensis ( Ye and Huang, 2020 ), Sanguina ( Procházková et al, 2019 ), or Bracteacoccus ( Chekanov et al, 2020 ) species were also found at high altitudes. Interestingly, in one occurrence at ∼3,000 m, Bracteacoccus aerius was detected.…”
Section: Discussionmentioning
confidence: 99%
“…It is also believed that carotenogenic microalgae can survive in a wide range of environmental conditions [136]. Nowadays, the analysis of carotenoids in algae is performed using high-performance liquid chromatography (HPLC).…”
Section: Application Of Raman Spectroscopy On Pigment Investigation I...mentioning
confidence: 99%
“…Three laboratory cultures (LC-I, LC-II, LC-III) of previously identified H. lacustris strains BMP/16, BMK/16 and BMM1/16 [34] were taken as a control for the principal component analysis (PCA,) ( Table 1). A detailed description of their bacterial composition has been given previously [26].…”
Section: Algal Strain Cultivation Conditions and Samplingmentioning
confidence: 99%
“…In the χ ij -based three-component space, NGS reads datasets of the samples from H. lacustris bacterial communities were broken up into several clusters ( Figure 3B,C). The datasets of the samples from the H. lacustris culture under the vegetative growth conditions in a photobioreactor clustered with control laboratory cultures from [34] on the projection of the principal components' space to the cross-section of the 1st and 2nd components ( Figure 3B). On the projection on the plane of the 2nd and 3rd components it was located separately ( Figure 3C).…”
Section: Changes In H Lacustris Bacterial Community Composition Durimentioning
confidence: 99%